Caste Discrimination, Land Reforms and Land Market Performance in Nepal - Jeetendra P. Aryal; Stein T. Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2011)
This paper assesses the implications of caste discrimination and past land reforms on the land rental market performance, land productivity and land use intensity in Nepal. The most severely discriminated group in the caste system is the Dalits, the so-called "untouchables". Dalits faced religious, occupational and even, territorial discrimination. The study uses data from western Nepal. The low-caste households remain poorer than other households, have significantly smaller land endowments, and have poorer access to off-farm employment. They access additional land through the land rental market but the past "Land-to-the-tiller" policies have had the unintended effect of reducing their land access even though they have significantly higher land productivity than high-caste households. Many high-caste households prefer to rent out their land to other (less productive) high-caste households out of fear of losing their land if they rent it out to low-caste households. Imperfections in land and labor markets contribute to enhance the inverse farm size-productivity relationship. A new type of tenure reform is needed that enhances tenure security and land redistribution through voluntary land market transactions
Keywords: J71; O12; Q12; Q15; Q24; 330; Caste discrimination; Land-to-the-tiller policies; land rental markets; share tenancy; inverse farm size-productivity relationship; Marshallian inefficiency